LINGUISTIC AND VISUAL MODES CONTRIBUTION TO THE HUMOR PRODUCTION OF PUNS IN INTERNET MEMES - Bahtiar, Zulfan; Chojimah, Nurul; Nurhayani, Ika (J-ELLiT (Journal of English Language, Literature, and Teaching), 2022)
This article aims to get a better understanding of the text-picture interaction and, in particular, the pragmatic consequences of 150 online memes that feature puns, one of the linguistic humor subgenres. This article will analyze a corpus of 150 memes. Using a comic taxonomy by McCloud (1994). The internet memes then were to be categorized. The default taxonomy of categories produced the following classification of internet memes: word specific (28), picture specific (2), additive (29), and interdependent (91). The findings show rather significant disparities among the findings. Some categories in the original taxomony are even absent in the data set.